Comparative Analysis of Serial and Parallel Robot Mechanisms for Industrial Automation - Prashant Roy (International Journal of Robotics and Automation in Mechanics, 2025)
Serial and parallel manipulators represent two major mechanical architectures in industrial automation, each with distinct strengths and trade-offs. This study presents a detailed comparative analysis of serial-chain (open-kinematic) robots and parallel-kinematic manipulators (PKMs) with a focus on industrial automation tasks. It covers kinematics, static accuracy and stiffness, dynamics and actuation requirements, control and calibration burdens, workspace and singularity behaviour, and practical industrial considerations (cost, integration, safety, maintenance). Serial robots, exemplified by articulated six-axis arms, offer broad reachable workspaces, high dexterity of end-effector orientation, a mature ecosystem for control and integration, and are well-suited for general assembly, machine-tending, or tasks requiring wide coverage. Conversely, parallel robots, such as hexapods or delta-type mechanisms, exhibit superior structural stiffness, high dynamic responsiveness, and better payload-to-mass ratios in constrained workspaces, making them advantageous for high-speed pick-and-place, precision machining, or vibration-sensitive operations. We present comparative tables summarising key performance dimensions, including illustrative figures of typical architectures and draw on recent literature to support claims. The analysis finds that while serial robots remain the general‐purpose workhorses in manufacturing, parallel robots are increasingly viable when stiffness, precision, and high dynamics dominate requirements. Emerging hybrid serial-parallel architectures are also reviewed. Finally, we provide decision guidance for practitioners selecting between architectures based on task demands and lifecycle considerations. The contribution lies in synthesising up-to-date comparative insights and offering an actionable framework for industrial automation system selection.
Keywords: Robot; Serial manipulators; Stewart-Gough hexapod; error propagation; parallel manipulators